Perkembangan Hukum Perdata Di Indonesia - Muzaki, Mhd Fikri; Siregar, Achmad Zulfikar (Jurnal Sosial Politik dan Hukum, 2024)
Changes and developments in civil law arise because law is dynamic, this is also influenced by human civilization which is increasingly shifting along with technological developments and global warming. Civil law is essentially closely related to strengthening the internal supervisory function which replaces the external supervisory function. The development of modern civil law is because its basis is always related to the relationship between the government regime and society, so that it can strengthen society's participatory role in certain aspects. One form of modernization of civil law that is developing includes; Contract agreement law, consumer protection law, and labor law, as a form of strengthening internal functions related to external control functions.